THE RELATIONSHIP BETWEEN DIET COMPLIANCE WITH BLOOD SUGAR LEVELS IN TYPE 2 DM PATIENTS IN BANTUL: THE RELATIONSHIP BETWEEN DIET COMPLIANCE WITH BLOOD SUGAR LEVELS IN TYPE 2 DM PATIENTS IN BANTUL - Putra, muhammad GA (Universitas Aufa Royhan, 2022)
Background : Diabetes Mellitus is a disease caused the body is unable to produce enough insulin and causes various complications, one of which is hyperglycemia. Diet settings are the most important key in the successful management of diabetes mellitus. Objective : The study aimeds to determine the relationship between dietary compliance with blood sugar levels among people with type 2 diabetes mellitus in Bantul. Methods : The type of research applied quantitive with a cross sectional design. That will be carried out on type 2 diabetes mellitus among people in the Bantul. Samples were recruited by purposive sampling technique in the Puskesmas Srandakan Bantul in the study was 55 people. The data were collected by using the diet compliance questionnaire and measuring blood sugar levels using medical record documentation. Kendal Tau correlation analysys was used to analized data. Result : Kendal Tau correlation test shown that between dietary compliance and blood sugar levels, obedience value of 0.000 (p<0.05), is that there is a significant relationtship between the variables of the diet compliance and blood sugar levels. so Kendal Tau r-value correlation 0,616, which means the better the dietary compliance, the better the blood sugar levels in type 2 diabetes mellitus patients. Conclusion : There is a relationship between diet compliance and blood sugar levels in type 2 diabetes mellitus patients in the Bantul. Keyword : Type 2 diabetes mellitus, diet compliance, blood sugar levels